Sustainable Spatial Solutions Flood Mitigation - Rajabuddin (IAHN-TP Palangka Raya, 2024)
Flooding and regional spatial planning are two things that are closely related to each other, if regional spatial planning is carried out properly and correctly then flooding will not occur. However, a factual phenomenon that often occurs during the rainy season, the threat of flooding often overshadows residential areas, and during the dry season, many areas experience drought in agricultural areas. The aims of this writing are: 1) to obtain the results of a sustainable spatial planning analysis that can be a solution for flood management, and 2) to obtain the results of a spatial planning analysis in an area that can be audited when a flood disaster occurs. The research method used is to use a socio-juridical approach (socio-legal), this research is supported by a statutory approach (statute approach), historical approach (historical approach), and conceptual approach (conceptual approach). In general, this research is analytical prescriptive. The results of this study are as follows. First. As a form of sustainable spatial planning solutions for flood management, there are five steps that can be taken, namely: 1). conduct an audit of space or land use in accordance with the functions and designations in the RTRW, master plan, RDTRK. 2). check the legality of the land/house. 3), the government, academia, the public and experts are expected to sit together to formulate directions and strategies that can be implemented to find a win-win solution for flood management. 4). Regional governments can normalize rivers, canals, revitalize lakes, lakes, reservoirs, and save beaches and mangrove forests whose land has been converted, and 5). The local government needs to carry out social engineering for residents who live close to water conservation areas. Second. In connection with this phenomenon, there are several audit steps to handle spatial planning, namely: 1) Conducting spatial audits in the form of evaluations related to the suitability of RTRW, RDTR, and RTBL spatial utilization activities. 2) The central government conducts an audit of compliance with spatial planning within the scope of the province. 3) The central government prepares and reports audit results and publishes them to the public. 4) The regional government must control and take action against those who violate the spatial plan. 5) The regional government conducts building and environmental audits, preferably for downtown areas which are seen as conformity with the basic building coefficients, availability of green basic coefficients. 6) The local government revitalizes existing channels throughout the city, both rivers and ditches, which may cause flooding or inundation.